The Principle of Autonomy of Contractual Will - Hasneziri , Luan (European Journal of Multidisciplinary Studies, 2022)
One of the fundamental principles on which the contractual law of any democratic state is based is the principle of contractual freedom. This principle is accepted by both Western legal systems, civil law and common law as well. Therefore, in dealing with this principle of contractual law, we shall have to refer to both the civil legislations of the states that are part of the civil law system, as well as those that are included in the common law legal system. One of the main issues of this paper concerns the meaning and content of the principle of autonomy of contractual will. In this matter, the most important aspects of this principle will be dealt with in summary, starting from the right of the parties to freely determine the content of the contract and ending with the limitations placed on the will of the parties in application of this principle. The elements of the principle of contractual freedom will be addressed in this paper, looking at them in a comparative perspective with the legislation of other countries, in addition to the Albanian civil legislation, highlighting the mutual features and differences between them. Another issue of this paper will be the application of the principle of autonomy of will to consumer contracts. Our focus herein in particular on the special rules that apply in this case, where it is worth noting that contemporary civil legislations have imposed a number of restrictions on the implementation of this principle, in order to protect the consumer. In this paper, the rules that are applied in the cases of standard or adhesion contracts will be treated, in a summarized way, in application of the principle of contractual freedom. At the end of the paper, the conclusions will be provided, as well as the bibliography on which it is based.